2004
DOI: 10.4269/ajtmh.2004.71.561
|View full text |Cite
|
Sign up to set email alerts
|

ELEVATED PLASMA LEVELS OF INTERFERON (IFN)-γ, IFN-γ INDUCING CYTOKINES, AND IFN-γ INDUCIBLE CXC CHEMOKINES IN VISCERAL LEISHMANIASIS

Abstract: Interferon (IFN)- gamma plays an important role during immune responses against leishmaniasis. Production of IFN-gamma is regulated by interleukin (IL)-12, IL-18, and IL-15. Interferon-gamma-inducible protein (IP)-10 and monokine induced by IFN-gamma (Mig) are CXC chemokines, the production of which, at least in part, is IFN-gamma dependent. A follow-up study of individuals infected with Leishmania donovani was undertaken in an area of Ethiopia endemic for visceral leishmaniasis (VL). Plasma levels of IFN-gamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
55
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 38 publications
10
55
1
2
Order By: Relevance
“…The plasma concentrations of most of the analysed cytokines (IFN-γ, TNF-α, IL-4 and IL-10) were higher in the subjects with active VL relative to the other groups, demonstrating an exacerbation of the immune response in these patients; this elevation in cytokine levels is in agreement with results from other studies (Hailu et al 2004, Peruhype-Magalhães et al 2005, Kurkjian et al 2006, Khoshdel et al 2009). Here, a mixed cytokine profile (Th1 and Th2) was detected in the patients with the active disease.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The plasma concentrations of most of the analysed cytokines (IFN-γ, TNF-α, IL-4 and IL-10) were higher in the subjects with active VL relative to the other groups, demonstrating an exacerbation of the immune response in these patients; this elevation in cytokine levels is in agreement with results from other studies (Hailu et al 2004, Peruhype-Magalhães et al 2005, Kurkjian et al 2006, Khoshdel et al 2009). Here, a mixed cytokine profile (Th1 and Th2) was detected in the patients with the active disease.…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, higher concentrations of IFN-γ were detected in the patients with the active disease, which is in agreement with results from other studies (Hailu et al 2004, Caldas et al 2005, Ansari et al 2006. IFN-γ is likely produced in lymphoid organs where Leishmania proliferates (Goto & Prianti 2009).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The involvement of chemokines in leishmaniasis was investigated primarily using murine models of leishmaniasis [13,35,44]. A few studies have examined chemokine responses locally in the skin or peripheral blood mononuclear cells of people with leishmaniasis [20,34]. However, no information is available on the pattern of chemokine expression in visceral organs during HVL or during CVL.…”
Section: Zoonotic Visceral Leishmaniasis (Zvl) Is Caused By Parasitesmentioning
confidence: 99%
“…Although some studies evaluating cytokines in serum samples have either not detected or found low concentrations of 69,70 , other studies have produced conflicting results. IFN-g was detected in 17 of 44 patients in Iran 2 and in 13 of 15 patients in Brazil 20 ; in addition, high levels have been confirmed in patients in Asia, Europe, Africa, and Brazil 9,15,31,32,50,52 . These differing results are most likely not related to the selected patient groups or to the Leishmania species involved, but rather to the samples that were analyzed.…”
mentioning
confidence: 92%